Perancangan Sistem Informasi Reservasi MP BARBER Berbasis Android - Gilang Amanah; Utami Mizani Putri; Pol Metra (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
MP BARBER is an exclusive barbershop for men located in Kedemangan Village, Muaro Jambi Regency. Customers have complained about the queues at MP BARBER, reflecting the direct impact of an unsatisfactory experience where customers feel uncomfortable. This situation highlights the importance of queue management and efforts to improve service efficiency, to maintain customer satisfaction and minimize the potential loss of customers in the future. Therefore, the researcher offers the design of an Android-based reservation information system for MP BARBER. The research uses a qualitative approach, the prototype development method, system design using UML, and is assisted by Corel Draw. The system design uses Android Studio, Visual Studio Code, and XAMPP as the database. System testing is carried out using the blackbox method and feasibility testing through 8 respondents, including the owner, employees, and customers of MP BARBER.